Improving Students Activities and Learning Outcomes in Ecosystem Materials through Student Team Achievement Division Learning Model - Dadang Suwanto (Journal Of Biology Education Research (JBER), 2021)
The learning outcomes of class X IPS 1 students in the Biology subject, Ecosystem material, are still not satisfactory. Of the 35 students, 30 students (86%) scored below the KKM. This is the background for Classroom Action Research (CAR). The Student Teams Achievement Divisions (STAD) method is used in this CAR to improve learning outcomes and student activity. The research subjects were 35 students of class X IPS 1 Academic Year 2018/2019, consisting of consisting of 19 male students and 16 female students. The results showed as many as 54% of students scored above the KKM in cycle I, and as many as 86% of students scored above the KKM in cycle II. From these data it can be concluded that the STAD Learning Model can increase student activity and learning outcomes in Biology learning, especially Ecosystem material in class X IPS 1 SMA Negeri 1 Ciampea.  Hasil belajar siswa kelas X IPS 1 dalam mata pelajaran Biologi, materi Ekosistem, masih belum memuaskan. Dari 35 siswa, sebanyak  30 siswa (86%)  memperoleh nilai di bawah KKM. Hal ini menjadi latar belakang dilakukan Penelitian Tindakan Kelas (PTK). Metode  Student Teams Achievement Divisions (STAD) digunakan dalam PTK ini untuk meningkatkan hasil belajar dan keaktifan siwa. Subyek penelitian adalah siwa kelas X IPS 1 Tahun Pelajaran 2018/ 2019 sebanyak 35 siwa, yang terdiri dari 19 siswa laki-laki dan 16 siswa perempuan.. Hasil penelitian menunjukkan sebanyak 54% siswa mendapat nilai di atas KKM pada siklus I , dan sebanyak 86% siwa mendapat nilai di atas KKM pada siklus II. Dari data tersebut dapat disimpulkan bahwa Model Pembelajaran STAD dapat meningkatkan aktivitas dan hasil belajar siswa pada pembelajaran Biologi khususnya materi Ekosistem.pada siswa kelas X IPS 1 SMA Negeri 1 Ciampea.